2008
DOI: 10.4137/ccrep.s817
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Invasive Pulmonary Nocardiosis and Aspergillosis in a Patient with T-Cell Lymphoma: A Case Report

Abstract: In patients with malignant hematological disorders receiving immunosuppressive therapy, invasive pulmonary infections are serious complications that are associated with high morbidity and mortality. In immunocompromised hosts with impaired cellular immunity, two or more organisms may coexist leading to a wide range of clinical and radiological manifestations.Reported here is an old man who was diagnosed to have angioimmunoblastic T-cell lymphoma at King Faisal Specialist Hospital and Research Centre in Riyadh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Revealing a predominance of immunocompromised hosts. The instances encompassed cases of immunosuppressive drug therapy, [ 2 , 21 , 31 ] hematologic malignancies, [ 18 , 24 , 25 ] organ transplantation, [ 15 , 16 , 19 , 20 ] chronic granulomatous disease, [ 9 , 14 ] and systemic lupus erythematosus, [ 29 ] and a case of a tooth extraction in a mildly immunosuppressed patient. [ 30 ] Such cases were also observed in nonimmunosuppressed hosts, including patients with diabetes, [ 28 ] allergic disorders, [ 26 ] bronchial thermoplasty therapy [ 27 ] ulcerative colitis during golimumab therapy, [ 23 ] and even accidental drowning incidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Revealing a predominance of immunocompromised hosts. The instances encompassed cases of immunosuppressive drug therapy, [ 2 , 21 , 31 ] hematologic malignancies, [ 18 , 24 , 25 ] organ transplantation, [ 15 , 16 , 19 , 20 ] chronic granulomatous disease, [ 9 , 14 ] and systemic lupus erythematosus, [ 29 ] and a case of a tooth extraction in a mildly immunosuppressed patient. [ 30 ] Such cases were also observed in nonimmunosuppressed hosts, including patients with diabetes, [ 28 ] allergic disorders, [ 26 ] bronchial thermoplasty therapy [ 27 ] ulcerative colitis during golimumab therapy, [ 23 ] and even accidental drowning incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Near-drowning incident Al-Anazi KA, [18] 2008 T-Cell Lymphoma, receiving immunosuppressive therapy Hamadani M, [19] 2008…”
Section: Reference Predisposing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Rivera et al in 2017 reported a case of paramediastinal abscess in an immunocompetent patient with no known lung disease 8. There have been several case reports of co-infection with Nocardia and Aspergillus to date, but coexisting N. cyriacigeorgica and Aspergillus infection is rarely reported 9–19. This may be partly because N. cyriacigeorgica is a newly identified strain of Nocardia .…”
Section: Discussionmentioning
confidence: 99%